2016
DOI: 10.1016/j.amjmed.2015.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Sensitive Copeptin and Cardiac Troponin in Diagnosing Non-ST-Segment Elevation Acute Coronary Syndromes—The COPACS Study

Abstract: A single-sampling strategy of combined ultra-sensitive copeptin and medium-sensitivity cardiac troponin I is noninferior to a 0- and 3-hour serial medium-sensitivity cardiac troponin I sampling in ruling out non-ST-segment elevation myocardial infarction and thus may allow an earlier discharge of patients who are ruled out for non-ST-segment elevation myocardial infarction (ClinicalTrials.gov Identifier NCT01962506).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Our findings corroborate previous data on the diagnostic and prognostic yield of competing rule-out strategies for MI (10,(32)(33)(34)(35)(36), providing evidence on their comparable clinical performance regardless of time of symptom onset, GRACE risk score and renal function status.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings corroborate previous data on the diagnostic and prognostic yield of competing rule-out strategies for MI (10,(32)(33)(34)(35)(36), providing evidence on their comparable clinical performance regardless of time of symptom onset, GRACE risk score and renal function status.…”
Section: Discussionsupporting
confidence: 90%
“…A study reported that the combined use of copeptin and cardiac troponin I is not inferior to serial cardiac troponin I measurement in ruling out NSTEMI. 22 However, this study used mediumsensitivity troponin assays. Another study investigated the single combined testing of troponin and copeptin to rule out AMI, and the proportion of major adverse cardiac events is not inferior in the copeptin group to that in the standard group.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of included studies. The 14 studies included a total of 7,998 patients, and the prevalence of NSTEMI was 14.2% (range 6.0-35.6%) [10,[15][16][17][18][19][20][21][22][23][24][25][26][27]. Only the CHOPIN study was a multinational study conducted in the USA and Europe, whereas all the other studies were conducted in Europe.…”
Section: Characteristics Of Study Subjectsmentioning
confidence: 99%